Surgical and Orthodontic Management of Impacted Dilacerated Maxillary Incisor in a 12-Year-Old: A Case Study - Khairani, Annisa; Sutadi, Heriandi; Fauziah, Eva (Journal of Syiah Kuala Dentistry Society, 2023)
Background: At age six, the mixed dentition phase begins, typically marked by the emergence of the lower permanent central incisors and first molars. It initiates a sequence of tooth eruptions. If one upper permanent central incisor remains unerupted by the age of nine while its counterpart has appeared, this may indicate an impacted tooth. Case Reports: Diagnostic serial radiographs often reveal nearly complete root formation without clinical emergence, leading to the diagnosis of tooth impaction. One common cause of impaction is trauma to the baby teeth and alterations in the front segment of the mouth due to the early loss of these primary teeth and the subsequent emergence of their permanent successors. Such trauma can influence the growth and development of the successor permanent teeth, including causing dilaceration. Disorders in tooth eruption can significantly affect aesthetics, speech, self-esteem, and social interactions, making treatment imperative. Conclusion: For impacted teeth, options like extraction with prosthetic replacement, orthodontic adjustment, or surgical exposure with traction are tailored to the patient's situation. Surgical exposure and traction were used on a 12-year-old with missing front teeth, extended by the complexity of the dilacerated root and fibrous tissue.